JBP485 promotes corneal epithelial wound healing - Nagata, Maho (Sci Rep, 2015)
Proper wound healing is vital for maintenance of corneal integrity and transparency. Corneal epithelial damage is one of the most frequently observed ocular disorders. Because clinical options are limited, further novel treatments are needed to improve clinical outcomes for this type of disease. In the present study, it was found that placental extract-derived dipeptide (JBP485) significantly increased the proliferation and migration of corneal epithelial cells (CECs). Moreover, JBP485 accelerated corneal epithelial wound healing in vivo without inflammation and neovascularization and was found to be effective for the treatment of corneal damage. These data indicate that JBP485 efficiently activates the viability of CECs and has potential as a novel treatment for various kinds of corneal epithelial disease.